Children Success Through Smart School of Early Childhood Education - Hanur, Binti Su’aidah (ACIECE, 2016)
Coming to school for early childhood is not merely come to study, write and read but moreover to develop all aspects of child’s development. In this age, children can be boosted to learn everything from their colorful surroundings and they always get success in their learning. Early childhood need more spaces to learn because they are active children and most of their time are used outside exploring their universe. This article tries to offer some alternative methods to select smart schools which suit with the early childhood best. The alternative methods offered in this paper was from Hastings’ s analysis and correspond to the existence of our smart schools in Indonesia. This paper discussed twenty things that are happening in schools which can be considered to make our child a success. In conclusion, There have been many offerings of smart school in Indonesia today. Making the right choice in choosing a good school which accepts children with their unique and characteristic is being one of consideration of parents. Knowing the system about the different types of school and how they work also must be considered. Parents should consider the best school for their children based on their child’s capability. Getting up to date which are happening in schools today is also a must in order parents can be aware to every risks will be faced by their child and wise parents will always focus on their child’s development than on their own need and prestige.